2018
DOI: 10.1155/2018/4953806
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Housekeeping Genes as Reference for Reverse-Transcription-qPCR Analysis in Busulfan-Injured Microvascular Endothelial Cells

Abstract: Endothelial cells (ECs) could express some important cytokines and signal molecules which play a key role in normal hematopoiesis and repopulation. Busulfan-induced vascular endothelial injury is an important feature after hematopoietic stem cell transplantation (HSCT). But the molecular mechanism of how the injured ECs affect hematopoietic reconstruction is still unknown. It is possibly through modulation of the change of some gene expression. RT-qPCR is one of the most popular methods used to accurately dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Primer sequences and probes are shown in (Table 2). For RT-qPCR, the synthesized cDNA samples 10 ng were amplified with the SYBR green master mix in a final volume of 20 ul, as described in our previously published article [18]. The mean threshold values are used to evaluate the molecular gene expression with normalization with mouse betaactin and GAPDH.…”
Section: Characterization Of Primary Bone Marrow Endothelial Cells By Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Primer sequences and probes are shown in (Table 2). For RT-qPCR, the synthesized cDNA samples 10 ng were amplified with the SYBR green master mix in a final volume of 20 ul, as described in our previously published article [18]. The mean threshold values are used to evaluate the molecular gene expression with normalization with mouse betaactin and GAPDH.…”
Section: Characterization Of Primary Bone Marrow Endothelial Cells By Real-time Quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%
“…Multiple studies have investigated candidate reference genes in iPSCs or ECs 10,19−23 , during reprogramming and differentiation 10,23 . In addition, various publications reported a selection of housekeeping genes in endothelial cells, such as microvascular EC 19 , human retinal EC 21 , and human blood-brain barrier EC 22 . The candidate reference genes examined in these studies were among the commonly used housekeeping genes in our study, including B2M, GAPDH, GUSB, HPRT1, HMBS, and YWHAZ.…”
Section: Discussionmentioning
confidence: 99%
“…No PCR product appearing on the total RNA gel showed that no genomic DNA contaminated the total RNA. Product integrity was also evaluated using 0.8% agarose gel electrophoresis and showed no contamination with DNA or degradation of RNA [23,24].…”
Section: Rna Extraction and Real Time Quantitative Rt-pcrmentioning
confidence: 99%